The Role of Educator in Handling the Victim of Papua Conflict at PLK Bima Sakti Cangkring B Karanganyar Demak - Mustawa , Ali (2012)
This study has a focus on How is the role of educator in handling the victim of Papua conflict at PLK Bima Sakti Cangkring B Kecamatan Karanganyar Kabupaten Demak? There were three objectives in this study. The first was to describe characteristics of educator in handling the victims of Papua conflict at PLK Bima Sakti Cangkring B Karanganyar Demak. The second was to elaborate the characteristics of the division of educator task in handling the victims of Papua conflict at PLK Bima Sakti Cangkring B Karanganyar Demak. And finally, this study aimed to describe characteristics of educator activities in handling the victims of Papua conflict at PLK Bima Sakti Cangkring B Karanganyar Demak. It is a qualitative research using ethnography design. This study was done at PLK Bima Sakti Cangkring B Karanganyar, Demak. This study involved several informants such as the Head of PLK Bima Sakti, educator, and students. The method for collecting data in this research paper process was observation, indepth interview, and documentation. While the technique of data analysis was done through data reduction, data display, and drawing conclusion. This finding suggests that there are 20 educators that came from Demak and outside of this region. The educators are recruited through a special selection and there is also a special way for students who have graduated from PLK Bima Sakti to become the educator. The qualification of educator is at least the high school graduates. Not only have competencies, educators also have skill and be able to use Arabic and English. The division of task is done by the head of Special Service Education and the foundation. The aspect considered in dividing the task includes the diversity of competencies and skills, and educators' interest. Educators are in charge of educating, guiding, and nurturing students. The educators teach in the formal learning in the morning, and learning in the Islamic boarding house in the afternoon. There are some educators who teach two subjects at once and have two positions in the PLK Bima Sakti. Educators teach and also give a life skill education to students who are the ethnic conflict victims. Tasks of educator are accounted for through a monthly report on the students' development associated to their respective field. Activities of educator in the formal learning include implementing the learning concept that emphasizes on three aspects such as religion, language, and skill; creating an independent and fun learning, and technology-based learning; and giving the special service to help students' difficulties. The learning activities in the Islamic boarding house include assisting, monitoring, and actively involved in activities in the boarding house, and conveying religious material through learning activity and habituation.